Effects of information communication technologies on economic growth, environmental quality, and labor productivity - Yong, Sze Wei (2022)
The first objective of this study is to investigate the impact of ICTs on economic growth, which is dependent on the intelligence threshold level for the 128 countries in 2019. ICTs are key driver of economic growth, and several studies have been conducted with varying perspectives on ICTs. Most research has been conducted on the relationship between ICTs and economic growth. However, research on the relationship between ICTs and intelligence-based economic growth is limited. Specialists in operating, investing, and expanding technology are required to use ICT infrastructure effectively. Employees with a high level of intelligence will ensure that ICT adoption runs smoothly and significantly increase productivity over workers with a low level of intelligence. This study investigates the role of intelligence in moderating the impact of ICTs on economic growth. The threshold regression model provides a more consistent and accurate indication of the intelligence threshold value, which can be used to show how intelligence influences the ICTs and economic growth nexus in both below and abovethreshold regimes. Hansen's (2000) threshold regression estimation reveals that ICTs stimulate economic growth when intelligence is below a certain threshold level but not above the threshold value. To improve economic growth, developing-country policymakers should prioritize human capital development through skill-based training, particularly in the digitalization era. The second objective of this study is to examine the ICTs threshold effect on economic growth and environmental quality nexus. Environmental quality has long been regarded as a critical factor in long-term growth and advancement in many countries. The CO2 emissions rate in developing countries increased to 63 percent in recent years due to industrialization procedures and significant energy-intensive technologies for national development and progress. According to the United Nation (2015), ICTs help to promote economic growth and address environmental challenges. Therefore, this study employs dynamic panel threshold regression by Seo et al. (2019) to examine the threshold effect of ICTs on economic growth and environmental quality for 69 developing countries from 2000 to 2019. The empirical results indicate that the ICTs variable is a statistically significant determinant of economic growth and environmental quality. Economic growth improves the environmental quality when the ICTs variable is below the threshold value. When the usage of ICTs exceeds the threshold value, economic growth degrades the environmental quality in developing countries. Thus, ICTs use in these countries to modernize, automate, and digitalize production processes requires close monitoring and legitimate concern from policymakers to ensure that ICTs usage is optimal and not excessive. Excessive ICTs use degrades environmental quality in developing countries. The third objective of this study is to evaluate the impacts of ICTs on labor productivity in 84 developing countries from 2000 to 2019, using the dynamic panel system generalized method of moments (GMM) and dynamic panel quantile regression estimations. According to ITU (2020), ICTs play a pivotal role in boosting productivity and employment in developing countries, thereby achieving one of the 2030 Agenda's priorities and a component of Sustainable Development Goal 8. This notion is supported by the rapid growth of the youth population in developing countries, as they are active ICTs user and will shape the future labor market. The empirical findings provide new evidence on the moderating effect of ICTs on human capital, financial development, and trade openness in influencing labor productivity in developing countries. ICTs have a positive and statistically significant moderating effect on labor productivity in developing countries through ICTs' interaction with the above three variables. Comparatively, the outcome from dynamic panel quantile regression reveals that ICTs improve labor productivity in the lower and middle quartiles than in the upper quantiles of developing countries. This study can help policymakers develop a long-term strategy for ICTs adoption and usage in developing countries to achieve industrial 4.0 goals.